Law and Gender perspective: A required meeting - Mantilla Falcón, Julissa (2017)
Traditionally, a gender analysis has not been incorporated to the development and analysis of the Law since its importance and utility is unknown, especially for the guarantee of human rights. At Law Schools there are other priorities in the curricula and the lack of a gender perspective will have an impact in the professional development of those future lawyers, especially if they became part of the National Prosecutor Office of the Justice Administration, for example. Thus, it is fundamental to understand the importance of the gender perspective in the law implementation, to realize the dimensions of this approach and to identify the gender stereotypes in the norms and case law.